Distribution of ABO and Rhesus Blood Groups among the Population of Mymensingh District and the Students of University of Dhaka, Bangladesh (Ibrahim Cardiac Medical Journal, 2011)
Keywords: ABO blood group; RhD blood groupIbrahim Card Med J 2011; 1(1):33-35